Establishment and Growth of Business Clusters with Public Aid - Skokan Karel; Poledníková Eva; Staníčková Michaela (Journal of Competitiveness, 2012)
Industry or business clusters have become a part of an industrial policy in most countries not only within the European Union and are considered an effective instrument for the growth of firms and regional competitiveness. Their development is promoted and supported by many financial schemes at regional, national and even supranational level. The development of industry clusters in Czechia has had a very short tradition so far as the concept of clusters has become known here only at the beginning of this century. Surprisingly public aid for cluster development was approved at the governmental level very soon and the top-down approach strategy followed. The objective of the paper is to identify the basic phases of cluster development in the Czech Republic and to describe the impact of public financing on cluster establishment and growth in Czech regions. The presented case of Moravia-Silesia shows the cluster dynamics in the region which made the use of EU structural funds efficient for their development.